COMPUTATIONAL THINKING FOR TEACHING ALGORITHM AND PROGRAMMING LOGIC IN DISTANCE LEARNING TECHNOLOGY COURSES - Milani, Berenice (2024)
Distance Education (DE) has established itself as a means to democratize access to education, especially for individuals residing in remote areas, facing geographical barriers, or requiring flexibility in study schedules. Additionally, regarding content learning, students lacking a solid foundation in mathematics and/or technology may encounter difficulties in solving problems logically and structurally, impacting the learning of essential content for their development. With a focus on training professionals in the field of Information Technology, one strategy that can be employed to motivate and assist early-year students in a distance technology course to understand programming-related content is Computational Thinking (CT). Based on these considerations, this study proposes to employ the fundamentals of decomposition, pattern recognition, abstraction, and algorithm to help first-year students in the distance course "Systems Analysis and Development" understand content in the "Algorithms and Programming Logic" discipline. To this end, bibliographic research was conducted through the Scopus and Scielo databases, along with action research through which an activity was designed for first-year students in the course. We hope the proposal can effectively contribute to developing key skills in future programmers, enabling them to perform effectively and competently in the field of information technology.